Walk to transit or drive to transit? - Schiller, P.; Kenworthy, Jeffery (Walk 21, 2011)
The most common form of access to urban transit is by foot. Early suburban and exurban commuting to urban centers was facilitated first by commuter rail along existing intercity rail lines and then by interurban services that were often electrified. Since these services generally connected town centers most access to them was by foot and occasionally by horse. The rise of automobility in the early decades of the twentieth century facilitated by increased roadbuilding and paving, led to greater automobile commuting or driving to stations. The provision of park and ride facilities was greatly influenced by shifts in U.S. transportation policy and funding, beginning in the 1960s. The park and ride idea has been imported by many transit systems around the world, although most have made significant departures from the American model in both form and provision. Walk-to and drive-to transit are compared and the consequences of investment in park and ride and “kiss and ride,” especially in the U.S. and Canadian contexts, are explored. It is found that drive-to transit comes with considerable environmental, fiscal and opportunity costs and that its funding could be applied more productively to improving local transit and pedestrians conditions.